Innovation of Elbow Fixture Welding Process Based on Design for Manufacture and Assembly (DFMA) - Novri Yunus; Anita Susilawati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The elbow fixture in the welding process is a supporting tool to holder the work-piece in the welding process. This tool is made in Do It Yourself (DIY) in micro-business. However, in its application there are problems. The solution provided to overcome these problems is the development of tools with the Design For Manufacture and Assembly (DFMA) method. The goal is to create a portable device design that is easy to carry and to calculate the time and cost of the manufacturing process and welding fixture assembly. The development of tools is carried out by looking for more complex problems through a consumer need questionnaire and a product development questionnaire. Data obtained from the development questionnaire can be used as a concept design (sketch) for analysis based on DFMA. The DFA (Design For Assembly) is carried out to simplify the assembly design and facilitate the assembly process. The choice of material is the basis for the quality of the product. The DFM (Design For Manufacture) is done to determine the component manufacturing process design, calculate the cost of materials and manufacturing costs. From the DFMA process, an innovation design for the welding process consists of 22 components with 12 different types of components. The design of innovative elbow aids in the welding process is called adjustable angles welding fixture. The cost used to manufacture this tool is Rp. 87,953 and the assembly and manufacturing time is 97 minutes 47 seconds.